Unemployment invariance - Marika Karanassou; Dennis J. Snower (Queen Mary University of London, Department of Economics, 2002)
This paper provides a critique of the "unemployment invariance hypothesis", according to which the behavior of the labor market ensures that the long-run unemployment rate is independent of the size of the capital stock, productivity and the labor force. Using Solow growth and endogenous growth models, we show that the labor market alone need not contain all the equilibrating mechanisms to ensure unemployment invariance; in particular, other markets may perform part of the equilibrium process as well. By implication, policies that raise the growth path of capital or increase the effective working-age population may influence the long-run unemployment rate.
Keywords: J38; J30; J23; J21; J68; J64; 330; Unemployment; employment; wage determination; labor supply; capital accumulation; productivity; technological change; economic growth; Natürliche Arbeitslosigkeit; Arbeitsmarkttheorie; Investition; Technischer Fortschritt; Wachstumstheorie; Neue Wachstumstheorie; Theorie